An Overview of Smart Cities (International Journal of Food and Nutritional Sciences, 2022)
Brilliant urban communities are expected to work on individuals' personal satisfaction, advance maintainable turn of events, and improve the effectiveness of metropolitan cycles. With such countless brilliant gadgets set up, security and protection concerns have ascended to the front, serious areas of strength for requiring. Because of the heterogeneity, adaptability, and dynamic nature of brilliant urban communities, traditional network safety insurance techniques can't be straightforwardly applied to these insightful applications. While creating and carrying out new techniques or frameworks, it is additionally fundamental to be aware of safety and protection gambles. Propelled by these contemplations, we look at the current situation with brilliant city security and protection to give an outline of both intellectual and industry regions and to make ready for future examination. This survey starts with an overview of smart cities to give readers with a comprehensive background. Then we go through the privacy and security problems that exist in today's smart apps, as well as the prerequisites for creating a robust and safe smart city. The next stage is to compile a list of current protective technologies. Finally, we suggest potential prospective research paths as well as open research problems.